PENGELOLAAN WILAYAH PESISIR DI PANTAI PANDAWA - Pujianiki, Ni Nyoman; Dirgayusa, I Gusti Ngurah Putra; Januatmika, I Made Rai (Jurnal Ilmiah Teknik Sipil; Jurnal Ilmiah Teknik Sipil, Vol. 24, No. 1, Januari 2020DO - 10.24843/JITS.2020.v24.i01.p02, 2020)
Management of coastal areas and small islands is regulated in Law Number 27 Year 2007 which is subsequently replaced by Law Number 1 Year 2014 which states that coastal area management is a process of planning, utilization, supervision and control of coastal resources with the aim of improving the welfare of the community carried out by the Government and Local Government. Pandawa Beach is one of the beach tourism in Bali that has progressed very rapidly in a short time compared to other beach tourism that have long been famous, as evidenced by visits and income every year. The increase has been supported by community-based coastal management. The purpose of this study is to review the community-based management of coastal areas that are implemented in Pandawa Beach. The descriptive qualitative method was used in this study by using 30 respondents consisting of managers and business actors in Pandawa Beach who were selected based on purposive sampling method . Data collection was conducted by observation and survey using open questionnaires and interviews. The results of data collection indicated that the management of coastal areas in Pandawa Beach consists of planned coastal areas through long-term planning and short-term planning. The c oastal areas is utilized as conservation areas, education and training, research and development, marine cultivation and tourism. Whereas the supervision of the coastal area in Pandawa Beach uses a village-based surveillance system that empowers the people of the village of Kutuh as a supervisor and the institution of the customary village as its coordinator. The control of the coastal area in Pandawa Beach uses an indigenous community-based control system that has been managed by the Kutuh Customary Village.